2020
DOI: 10.3390/cells9030676
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cx43 in Murine Sertoli Cells Leads to Altered Prepubertal Sertoli Cell Maturation and Impairment of the Mitosis-Meiosis Switch

Abstract: Male factor infertility is a problem in today’s society but many underlying causes are still unknown. The generation of a conditional Sertoli cell (SC)-specific connexin 43 (Cx43) knockout mouse line (SCCx43KO) has provided a translational model. Expression of the gap junction protein Cx43 between adjacent SCs as well as between SCs and germ cells (GCs) is known to be essential for the initiation and maintenance of spermatogenesis in different species and men. Adult SCCx43KO males show altered spermatogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 178 publications
1
7
0
Order By: Relevance
“…Thus, aims of the present study were, (1) the establishment of two new conditional KO mouse lines with a GC specific deletion of Cx43 either in premeiotic spermatogonia and early spermatocytes (pGCCx43KO) or in meiotic spermatids (mGCCx43KO) using the Cre/LoxP recombination system to cover the entire postnatal male GC population, (2) investigation of functions of Cx43 in these specific GC populations, and (3) elucidation of possible consequences of the KO of Cx43 in male GC on testicular development and spermatogenesis. Based upon the present data, KO of Cx43 in spermatogonia (pGCCx43KO) or spermatids (mGCCx43KO) did not seem to have dramatic impacts on testicular histology and successful completion of spermatogenesis in adult mice, as it is known for Cx43 in somatic SC [ 31 , 32 , 33 , 35 , 36 , 37 , 44 , 45 , 46 ]. This might be because GC-Cx43 is not essential for successful spermatogenesis or due to compensation by another, yet not identified, Cx in GC forming heterotypic GJ channels with Cx43 in SC.…”
Section: Introductionmentioning
confidence: 47%
See 3 more Smart Citations
“…Thus, aims of the present study were, (1) the establishment of two new conditional KO mouse lines with a GC specific deletion of Cx43 either in premeiotic spermatogonia and early spermatocytes (pGCCx43KO) or in meiotic spermatids (mGCCx43KO) using the Cre/LoxP recombination system to cover the entire postnatal male GC population, (2) investigation of functions of Cx43 in these specific GC populations, and (3) elucidation of possible consequences of the KO of Cx43 in male GC on testicular development and spermatogenesis. Based upon the present data, KO of Cx43 in spermatogonia (pGCCx43KO) or spermatids (mGCCx43KO) did not seem to have dramatic impacts on testicular histology and successful completion of spermatogenesis in adult mice, as it is known for Cx43 in somatic SC [ 31 , 32 , 33 , 35 , 36 , 37 , 44 , 45 , 46 ]. This might be because GC-Cx43 is not essential for successful spermatogenesis or due to compensation by another, yet not identified, Cx in GC forming heterotypic GJ channels with Cx43 in SC.…”
Section: Introductionmentioning
confidence: 47%
“…Several studies have shown that Cx43 is essential for spermatogenesis [ 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 44 , 45 , 46 , 47 ]. However, the contribution of known hemichannels provided by GC to this important role could not be determined and consequently is unknown so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tight junctions between Sertoli cells in the blood–testis barrier (BTB) are essential for the migration and maturation of male germ cells during spermatogenesis. Conditional knockout of Cx43 (connexin-43) mice assume the downregulated genes critical for mitosis and meiosis, e.g., Stra8 , Dazl , and members of the DM (dsxand map-3) gene family, and the upregulated genes related to Sertoli cell maturation and proliferation [ 81 , 82 ]. The expression levels of cross-epithelial resistance and tight junctions are significantly increased in primary Sertoli cells of mice lacking Cx43 .…”
Section: Novel Gene Regulation In Testicular Microenvironmentmentioning
confidence: 99%